2023
DOI: 10.1038/s42003-023-04823-0
|View full text |Cite
|
Sign up to set email alerts
|

Degeneracy in epilepsy: multiple routes to hyperexcitable brain circuits and their repair

Abstract: Due to its complex and multifaceted nature, developing effective treatments for epilepsy is still a major challenge. To deal with this complexity we introduce the concept of degeneracy to the field of epilepsy research: the ability of disparate elements to cause an analogous function or malfunction. Here, we review examples of epilepsy-related degeneracy at multiple levels of brain organisation, ranging from the cellular to the network and systems level. Based on these insights, we outline new multiscale and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 301 publications
(373 reference statements)
1
11
0
Order By: Relevance
“…We compared our results with the experimental data of Šišková et al (2014), which showed a firing mode change from single spikes to bursting observed in APP/PS1 cells. Our results are largely in line with the concept of degeneracy (Edelman & Gally, 2001;Tononi et al, 1999), according to which similar physiological but also similar pathological states such as neural hyperexcitability can emerge from multiple distinct mechanisms (Kamaleddin, 2022;Medlock et al, 2022;Neymotin et al, 2016;O'Leary, 2018;Ratté & Prescott, 2016;Stöber et al, 2022).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…We compared our results with the experimental data of Šišková et al (2014), which showed a firing mode change from single spikes to bursting observed in APP/PS1 cells. Our results are largely in line with the concept of degeneracy (Edelman & Gally, 2001;Tononi et al, 1999), according to which similar physiological but also similar pathological states such as neural hyperexcitability can emerge from multiple distinct mechanisms (Kamaleddin, 2022;Medlock et al, 2022;Neymotin et al, 2016;O'Leary, 2018;Ratté & Prescott, 2016;Stöber et al, 2022).…”
Section: Introductionsupporting
confidence: 87%
“…Rich et al, 2022) and homeostasis. However, the homeostatic compensation might only be possible for a limited range of parameters or fail due to the complex interactions in the high-dimensional parameter space of the extrinsic and intrinsic neuronal mechanisms (O'Leary, 2018;Stöber et al, 2022;Yang et al, 2022). Even though the high-dimensional parameter space might offer more possible solutions for firing rate homeostasis (Schneider et al, 2021), these solutions might be difficult to find due to the necessary adjustment of several ion channels and/or extrinsic parameters for multiple properties at the same time (Yang et al, 2022; but see also Jedlicka et al, 2022).…”
Section: Limitations and Applicabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We found that LPG was not necessary to maintain coordination among gastric mill neurons and there was little difference in the timing relationships in the absence of LPG. Given the variability of the Gly 1 -SIFamide gastric mill rhythm, our analysis might not have been sensitive enough to detect changes in coordination in the absence of LPG, or there might be degeneracy such that other synapses contribute the same function as the LPG neurons (80, 81). However, when other chemical synapses among gastric mill neurons were blocked with picrotoxin, LPG fully coordinated the activity of the other gastric mill network neurons, but with different timing relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Degeneracy also includes neuromodulatory actions, in which distinct modulators converge on the same ionic current to stabilize neuron bursting activity (5, 9496). Furthermore, degeneracy of ion channels or synapses contributes to different mechanisms for the same motor pattern under different modulatory states (60, 61, 81). In the Gly 1 -SIFamide modulatory state, partial synaptic degeneracy among LG, IC, LPG, and DG neurons may be important for enabling the gastric mill network to carry out multiple coordination patterns.…”
Section: Discussionmentioning
confidence: 99%